Influencing the Stability of Diaminomethane‐Containing Azacrown Ether Ligands in the Presence of Transition‐Metal Ions. Issue 18 (10th May 2013) - Gee, William J.; Batten, Stuart R.
Abstract: The evaluation of a new azacrown ether ligand bis{[3‐(pyridin‐4‐yl)‐1 H ‐pyrazol‐1‐yl]methyl}diaza‐18‐crown‐6 (b3pd ), which contains pendant p ‐pyridylpyrazole arms connected by diaminomethane linkers, identified a tendency to undergo retro‐Mannich fragmentation in the presence of transition‐metal ions. However, treatment ofb3pd with potassium perchlorate or potassium iodide prior to complexation with transition‐metal ions imparted a resistance to fragmentation, such that crystallisation of coordination polymers from concentrated solutions after several weeks was possible. Four solid‐state structures containing Kb3pd were isolated: a perchlorate salt (1 ), a divalent manganese 1D coordination polymer [Mn(Kb3pd )(DMF)4 ]· 2ClO4 · I3 (2, DMF = N, N ‐dimethylformamide), a cuprous 2D coordination network [Cu2 (Kb3pd )2 (I3 )(I)3 ]· 3H2 O (3 ) and a cuprous 1D coordination polymer [Cu(Kb3pd )(I)2 ] (4 ). Additionally, the retro‐Mannich process was investigated by in situ FTIR spectroscopy, mass spectrometry, crystallography and by the isolation of a cobalt complex ligated by a partially fragmented ligand, mono{[3‐(pyridin‐4‐yl)‐1 H ‐pyrazol‐1‐yl]methyl}diaza‐18‐crown‐6 (m3pd ). The composition of the cobalt complex was found to be [CoCl3 (Hm3pd )]· H2 O (5 ). Abstract : Diaza‐18‐crown‐6 ligands functionalised with diaminomethane linkers are unstable in the presence of selected divalent transition‐metal ions. Pretreatment of the ligands with potassium salts prevents degradation by blocking the central coordination region. Iodide redox chemistry also affects the coordination‐polymer motif.